2019
DOI: 10.1017/rdc.2019.81
|View full text |Cite
|
Sign up to set email alerts
|

Fossil Carbon Load in Urban Vegetation for Debrecen, Hungary

Abstract: Deciduous tree leaf and grass samples were collected in Debrecen, the second largest city in Hungary. The aim of the study was to determine the rate of fossil fuel-derived carbon in urban vegetation. At the locations sampled, C3 and C4 plants close to roads were collected in September 2017. In total, 82 tree and grass leaf samples were gathered at 36 different sampling points all over the city of Debrecen. The radiocarbon (14C) results of the samples were compared to the local urban background atmospheric 14CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In Quarta et al (2007), the highest fossil carbon fraction is only 2.6% while our highest value is 6.3%. In our former study (Varga et al 2019) the highest measured fossil carbon content was little higher, 9.6%, in a frequent urban area, at a busy crossroad in a Hungarian city, Debrecen. Our study shows that the radiocarbon level in vegetation, which reflects the atmospheric 14 CO 2 concentration with a good approximation, is approaching the preindustrial level.…”
Section: Resultsmentioning
confidence: 67%
“…In Quarta et al (2007), the highest fossil carbon fraction is only 2.6% while our highest value is 6.3%. In our former study (Varga et al 2019) the highest measured fossil carbon content was little higher, 9.6%, in a frequent urban area, at a busy crossroad in a Hungarian city, Debrecen. Our study shows that the radiocarbon level in vegetation, which reflects the atmospheric 14 CO 2 concentration with a good approximation, is approaching the preindustrial level.…”
Section: Resultsmentioning
confidence: 67%
“…The other sources of dust pollution are traffic, usually with increased heavy metal content (Ram et al, 2014;Jandacka et al, 2017;Budai and Clement, 2018), and as in all European countries, the Saharan dust (Borbély-Kiss et al, 1999, 2004Varga et al, 2013;Varga and Roettig, 2018). Based on dust adsorption of tree leaves, it was found that trees also act as sediment traps for urban dust (Braun et al, 2007;Molnár et al, 2018;Varga et al, 2019) and are good indicators of dust pollution level due to physiological responses . As tree species adsorb dust in their leaves differently, according to the different number of leaves and the roughness of their surface (Simon et al, 2014), mapping the tree species composition can help in the selection of appropriate species in the planning of urban green infrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…Using the JFJ radiocarbon record (and calculated April-July mean values) as a reference for a clean-air site (Levin and Kromer 2004), less influenced by anthropogenic fossil fuel emissions, we estimated the fossil carbon contribution within the wheat tissue by Fossil C% 1 F 14 C seed F 14 C JFJ 100 (Quarta et al 2007;Varga et al 2019). Between 1987-2016, fossil C contribution in the wheat tissue is mostly lower than 1%, slightly above 1% in 1990 and 1992, and with stronger excursions in 2010 and 2011 by 1-1.5% fossil C (Fossil_C(%) mean :0.7 ± 0.3; see Figure 3).…”
Section: Discussionmentioning
confidence: 99%